Risks, threats, and vulnerabilities related to social media platforms and search engines. Regulations and national legal frameworks - Dănuţ MAFTEI; Lorin Nicolae BOGDAN DUICĂ (Bulletin of "Carol I" National Defense University)
Online social media platforms and search engines are used more and more by violent people, criminal offenders, cybercriminals, and other state or non-state malicious actors, who are involved in activities connected to hybrid threats and foreign interference, causing challenges for children, girls, women, citizens, societies, economies, critical services, democracy, and homeland security. Social media platforms and search engines could do more to address these issues so as to ensure a free, open, safe, secure, and reliable internet for everybody and to maximize its positive effects. Neglecting the proliferation of illegal activities not only erodes trust in online platforms but also places at risk the security and privacy of its users. To counter efficiently all the challenges, urgent new regulatory frameworks are needed. The regulations should be applied to social media platforms, search engines, and services that allow users to post content online or to interact with each other.